OPTIMASI JARINGAN DISTRIBUSI LISTRIK SATU FASA SEBAGAI PENGONTROL BEBAN LISTRIK BERBASIS KOMPUTER - Suhendar Suhendar (LPPM Universitas Bina Sarana Informatika, 2010)
The main function of electric distribution network is to distribute electricity from central power plants through transmission network and reduce the voltage to 380 volts AC and 220 volts AC by using the distribution transformer. The 220 volts AC is a voltage from a onephase distribution network which is mostly used for household and office consumption. The electrical network can be optimized used as transmission to controlling electrical loads that connected with him. It is expected that with this system we can utilize the onephase electric network, work with computer continuously and effectively, and we can also control loads which is connected to the network effectively and efficiently. By using this system, the computer will directly receive alarm signal when there is a problem with one or all electrical load device. This signal is then displayed on the computer screen. Keywords: Distribution Network, Electrical Load, Frequency Shift Keying, Modulator, Demodulator